Integrated control of the Varroa destructor mite (Mesostigmata: Varroidae) with oxalic acid in Africanized honeybee colonies in the tropical conditions of Costa Rica - Calderón-Fallas, Rafael A. (2024)
The effectiveness of oxalic acid in controlling the Varroa destructor mite was evaluated in the present study. The experiment was conducted in an apiary consisting of 16 Africanized honeybee (AHB) colonies in Atenas, Alajuela. The colonies were divided into four groups to apply the following oxalic acid treatments: 1) trickling method: the solution was applied to the top of the frames with a syringe; 2) towel method: a towel was placed on the frame; 3) impregnated cardboard method: four impregnated strips were used per colony; and 4) control group: no oxalic acid was applied. Treatments were administered in the brood chamber, and observations were made to determine any possible adverse effects. Flumethrin was subsequently administered as a shock treatment for five weeks. The most effective method for controlling Varroa was the towel treatment, which achieved 74.4% effectiveness, while the trickling and cardboard strip methods produced 63.0% and 50.0% effectiveness, respectively. The control group registered a natural mite fall of 34.1%. Based on the results, it can be concluded that oxalic acid demonstrated effectiveness in treating V. destructor in AHB colonies under tropical conditions. When comparing the application methods, the towel method was the most effective, followed by the trickling method, making these approaches viable alternatives in the integrated management of the Varroa mite. The concentrations of oxalic acid used in the study were safe for AHBs, as no evident adverse effects were observed on the colonies.